Cross-Border Transmission of Salmonella Choleraesuis var. Kunzendorf in European Pigs and Wild Boar: Infection, Genetics, and Evolution - Leekitcharoenphon, Pimlapas; Sørensen, Gitte; Löfström, Charlotta; Battisti, Antonio; Szabo, Istvan; Wasyl, Dariusz; Slowey, Rosemarie; Zhao, Shaohua; Brisabois, Anne; Kornschober, Christian; Kärssin, Age; Szilárd, Jánosi; et al. (Frontiers in Microbiology, 2019)
Salmonella enterica subspecies enterica serotype Choleraesuis is a swine adapted serovar. S. Choleraesuis variant Kunzendorf are responsible for the majority of outbreaks among pigs. S. Choleraesuis is rare in Europe, although there have been serious outbreaks in pigs including two outbreaks in Denmark in 1999-2000 and 2012-2013. Here, we elucidate the epidemiology, possible transmission routes and sources, and clonality of European S. Choleraesuis isolates including the Danish outbreak isolates. A total of 102 S. Choleraesuis isolates from different European countries and the United States of America, covering available isolates from the last two decades were selected for whole genome sequencing. We applied a temporally structured sequence analysis within a Bayesian framework to reconstruct a temporal and spatial phylogenetic tree. MLST type, resistance genes, plasmid replicons and accessory genes were identified using bioinformatics tools. Fifty-eight isolates including 11 out of 12 strains from wild boars were pan-susceptible. The remaining isolates carried multiple resistance genes. Eleven different plasmid replicons in eight plasmids were determined among the isolates. Accessory genes were associated to the identified resistance genes and plasmids. The European S. Choleraesuis was estimated to have emerged in ~1837 (95% credible interval, 1733 - 1983) with the mutation rate of 1.02 SNPs/genome/year. The isolates were clustered according to countries and neighbour countries. There were transmission events between strains from the USA and European countries. Wild boar and pig isolates were genetically linked suggesting cross-border transmission and transmission due to a wildlife reservoir. The phylogenetic tree shows that multiple introductions were responsible for the outbreak of 2012-2013 in Denmark, and suggests that poorly disinfected vehicles crossing the border into Denmark were potentially the source of the outbreak. Low levels of single nucleotide polymorphisms (SNP) differences (0-4 SNPs) can be observed between clonal strains isolated from different organs of the same animal. Proper disinfection of livestock vehicles and improved quality control of livestock feed are recommended to prevent future spread of S. Choleraesuis or other more serious infectious diseases such as African swine fever (ASF) into the European pig production system.